Long Work Hours and Health in China - Peng Nie; Steffen Otterbach; Alfonso Sousa-Poza (Institute for the Study of Labor (IZA), 2015)
Using several waves of the China Health and Nutrition Survey (CHNS), this study analyzes the effect of long work hours on health and lifestyles in a sample of 18- to 65-year-old Chinese workers. Although working long hours does significantly increase the probabilities of high blood pressure and poorer reported health, the effects are small. Also small are the negative effects of long work hours on sleep time, fat intake, and the probabilities of sports participation or watching TV. We find no positive association between work time and different measures of obesity and no evidence of any association with calorie intake, food preparation and cooking time, or the sedentary activities of reading, writing, or drawing. In general, after controlling for a rich set of covariates and unobserved individual heterogeneity, we find little evidence that long work hours affect either the health or lifestyles of Chinese workers.
Keywords: I10; I12; J22; J81; 330; long work hours; health; lifestyle; China